THE FINANCIAL SECTOR OF THE STATE - THE STRUCTURE OF THE BANKING SYSTEM WITH A BANKING SECTOR IN CENTRAL AND EASTERN EUROPEAN COUNTRIES - Stošić Mihajlović, Ljiljana (Journal of process management and new technologies, 2017)
The financial sector of each country in the world has its own specificities that depend on many factors. In this paper we will talk about the structure of the financial system in our country from the aspect of the banking sector. Banks are specialized institutions that have a special role in the development of the country’s economic system, as their basic function is to supply the economy with the necessary amount of loans and money. Banking business is a special economic activity. It is determined by the type and content of banking operations. In general terms, banking transactions are divided into two groups: active and passive. The Bank is established as a joint-stock company, which is regulated by the laws on banks and international regulatory frameworks.